Business Intelligence Based on Kimball Nine-Steps Methodology for Monitoring the Feasibility of Goods in Market - I Putu Agus Eka Pratama; I Made Sunia Raharja (Indonesian Scientific Journal, 2023)
Consumer protection is of great concern to the Government of Indonesia through the supervision of goods on the market by the Department of Industry and Trade in each province. The Bali Provincial Office of Industry and Trade has transactional data from various data sources but has not been able to optimize it to support monitoring of goods circulating in the market. This research designs and implements a Data Warehouse-based Business Intelligence system using the Kimball Nine-Steps Methodology and Pentaho BI tools, to facilitate the storage and processing of goods data on the market, and monitor their feasibility. The results of this research show that the system can assist the Bali Province Industry and Trade Office in monitoring the feasibility of goods circulating in the market through the selection process for determining query priorities and query modes, as well as supporting decision-making processes and determining business strategies.